Using poems in increasing phonological awareness among children - Lim, C.T.; Chew, F.P. (2017)
This study was conducted to analyze the effects of using phonology method and traditional method in Malay language poems on phonological awareness among 62 children in government pre-schools. Quasi-experimental study was conducted to compare two methods. The conceptual framework applied in the study was based on the preparation of reading by Stewart (2004) and Theory of Cognitive Development (piaget, 1977). The experimental group (n = 30) was trained to read the poems by using phonology method whereas the control group (n=32) was trained by applying traditional method. Both groups were given pre-tests and post-tests to compare the level of phonological awareness in recognition of the number of syllables in a word, rhyming syllable discrimination in words, producing rhyming syllable, early and ended phonemic sound. The findings showed that usage of the rhyming poems has enhanced the level of phonological awareness among preschool children after the treatment significant. In contrary, the traditional method gave no effect on phonological awareness. However analysis of Mann Whitney U-test found no significant difference between the score between the male and female in experimental group. Therefore usage of poems to enhance phonological awareness can be used optimally by teachers in preschool because genre of poem is identified as an effective way to increase children's literacy.